Gerenciamento de riscos de operações e sustentabilidade organizacional: um estudo entre as empresas certificadas - Britto, José Geraldo Falcão (2015)
As of 2010, the main publicly traded organizations have been going through an improvement process of disclosing with transparency the results of their operations that involves the improvement of financial statements and supplementary reports, by adopting the standardization process promoted by the International Accounting Standards Board and International Financial Reporting Standards (IASB / IFRS). It also includes the disclosure of operational risks or operations to meet the new legislation will be effective on January 2016 (CVM Instruction 552). This process has promoted adaptive approach and adoption of new practices of reporting financial and accounting information, as well as has promoted the way the organizations manage their internal processes and operational controls. Especially in financial, banking and insurance sectors that fund productive activities, and motivated by the improvements of due diligence analysis of their customers and borrowers, they have better framed the analysis and identification of operational risks of organizations and are also following the changes promoted by the Organization for Cooperation of Economic Development (OECD). In this way, this study aimed to monitor, update, and analyze the current Organizational practices with regards to their Sustainability Operational Risk reports and the levels of compliance compared with existing risk management framework through structured interviews. To analyze the practices of organizations it has been done 02 studies, using primary data (survey made with organizations employees) and secondary data (financial statements, published integrated reports of sustainability risks). To better support the study, an open survey was conducted (primary data) with companies that are part of ABNT (Brazilian Association of Technical Standards and CEE63 committees - Risk Management), where the results showed that the organizations, for instance, Petrobrás, Netshoes, Inmetro, Furnas, Syngenta, Empresa RBS communication, Sabesp among others, have operational risks management practices and they are consistent with the criteria established by the framework, and they are in implementation phase and in constant process improvement. After applying the sample selection criteria (not probability) and the secondary data, the company named Fibria Celulose has been selected through the analysis of its ISE sustainability reporting, financial statements and integrated risk reporting (years 2013 and 2014 ), and this meets concept terms as well, by contemplating norms/standards and frameworks (standards ISO 26001, 16001, 31000), and is, as described in its own published reports, in preparation phase to meet new requirements of Securities and Exchange Commission (CVM). These processes of adapting organizations, the new requirements recently summarized in the standardization of Accounting practices; the disclosure of risk indexes; the materiality of operational risks; the certification of products/management systems of risk/sustainability and adoption of Environmental & Social Accounting are shown as a new phase of observation of the economic activities in Brazil